Response to "Comment on Nanometer-Scale Corrosion of Copper in De-Aerated Deionized Water" [J. Electrochem. Soc., 161, C107 (2014)]. Issue 3 (10th December 2015) - Cleveland, Christopher; Orazem, Mark E.; Moghaddam, Saeed
Abstract : This response is provided to comments by Spahiu and Puigdomenech criticizing the conclusion of Cleveland et al. [ J. Electrochem. Soc., 161, C107 (2014)] that, in the absence of hydrogen, copper will corrode in deaerated deionized water. Spahiu and Puigdomenech base their critique on anomalies in the Pourbaix diagram presented by Cleveland et al., on concerns that the experimental system was inadequately deaerated, and on differences between the corrosion rates predicted in our work and in the work of Hultquist et al. [ Proceedings of the 2008 International Corrosion Congress, Paper 3884, p. 1 (2008)]. In the present work, explanations are provided supporting our thermodynamic analysis and the experimental results. New numerical simulations show that the difference in estimated corrosion rates between our system and that published by Hultquist et al. are the natural consequence of scale and transport differences between the two systems. Thus, the comment that the difference in estimated corrosion rates between our system and that of Hultquist somehow invalidates our results is without basis. The concerns raised by Spahiu and Puigdoimenech do not invalidate the conclusions presented in Cleveland et al.